2023
DOI: 10.1002/ptr.7751
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MAPK/NF‐kB and activation of Nrf2 signaling by Ajugarin‐I in EAE model of multiple sclerosis

Abstract: Multiple sclerosis (MS) is a debilitating neurodegenerative autoimmune disease of the central nervous system (CNS). The current study aimed to investigate the neuroprotective properties of Ajugarin-I (Aju-I) against the experimental autoimmune encephalomyelitis (EAE) model of MS and explored the underlying mechanism involved. The protective potential of Aju-I was first confirmed against glutamateinduced HT22 cells and hydrogen peroxide (H 2 O 2 )-induced BV2 cells. Next, an EAE model has been established to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…In brief, these findings suggest that ISO inhibits chondrocyte apoptosis induced by H2O2, which may be mediated by the MAPK signaling pathway. ISO has been shown in numerous studies to prevent apoptosis caused by the MAPK signaling pathway [27,[45][46][47]. This phenomenon is also confirmed in our current study, which provides a theoretical foundation for ISO osteoarthritis treatment.…”
Section: Discussionsupporting
confidence: 89%
“…In brief, these findings suggest that ISO inhibits chondrocyte apoptosis induced by H2O2, which may be mediated by the MAPK signaling pathway. ISO has been shown in numerous studies to prevent apoptosis caused by the MAPK signaling pathway [27,[45][46][47]. This phenomenon is also confirmed in our current study, which provides a theoretical foundation for ISO osteoarthritis treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our study has revealed a previously unidentified feedback loop that triggers the activation of Nrf2 by LV in response to MAPK/NF-κB and HIF-1α coordination, inhibiting BEAS-2B damage during hypoxic stress. Additionally, the anti-hypoxia capability of LV towards BEAS-2B cells and lung tissue may also be attributed to its anti-apoptotic activity, as the coupling between MAPK/NF-κB and HIF-1α during stress induces nuclear senescence prior to apoptosis [ 55 , 56 ]. MAPK/NF-κB regulates local O 2 levels by modulating HIF-1α activation in BEAS-2B and lung tissue during hypoxia, potentially playing a role in chronic lung diseases.…”
Section: Discussionmentioning
confidence: 99%